Eros i Tanatos – „Róża” Jarosława Iwaszkiewicza i „Ubranie prawie nowe” w reżyserii Włodzimierza Haupego - Majca-Lipa, Katarzyna (Załącznik Kulturoznawczy, 2024)
The text is devoted to Jarosław Iwaszkiewicz’s story Róża (en. The Rose), with its firm adaptation, Ubrania prawie nowe (en. Almost Brand New Clothes) directed by Włodzimierz Haupe. The analysis, prioritizing the primacy of literary material over its cinematic counterpart, is grounded in intermedial assessments (Chmielecki 2008), literary studies (Przybylski 1970, Giełdoń-Paszek 2014), philosophical perspectives (Leszczyński 2003), and linguistic considerations (Burkot 1970). Furthermore, the historical as well as social and cultural context of the narrative has been delineated (Kuciel-Frydryszak 2018; 2023). The article’s objective is to demonstrate that both the literary and cinematic texts remain remarkably pertinent, encompassing both thematic and existential dimensions.